Self-efficacy, self-esteem, and happiness in older adults: A cross-sectional study - Towhid Babazadeh; Soheila Ranjbaran; Sara Pourrazavi; Khalil Maleki Chollou; Akbar Nadi; Erfan Saeedi Tazekand (PLoS ONE, 2025)
Background Happiness is crucial for well-being in older people, but it can be challenged by various health issues. While previous research has explored individual predictors of happiness, there is limited understanding of how self-efficacy—the belief in one’s ability to manage challenges—and self-esteem, or positive self-regard, together influence happiness in elderly populations. Hence, this research aimed to fill this gap by investigating the association of self-efficacy and self-esteem with happiness in elders. Methods A cross-sectional study was conducted with 400 individuals aged 60 years or older who visited health centers in Sarab, Iran, from April to June 2023. Data were collected using valid and reliable instruments, including the Oxford Happiness Questionnaire, Sherer’s Self-Efficacy Scale, and the Rosenberg Self-Esteem Scale. To analyze the data, bivariate comparisons of quantitative variables were performed using independent samples t-tests and one-way ANOVA. Additionally, hierarchical regression analysis was conducted on happiness using two distinct sets of independent variables. Results According to the results, there was a statistically significant association between marital status (p-value =  0.021), income (p-value <  0.001), education (p-value <  0.001), and physical activity (p-value <  0.001) with happiness. Happiness showed strong positive correlations with self-efficacy (r =  0.747; p-value <  0.001) and self-esteem (r =  0.306; p-value <  0.001). Hierarchical multiple linear regression analysis revealed that demographic factors accounted for 15.3% of the variance in happiness, while self-efficacy and self-esteem explained an additional 43.0%, totaling 58.7%. Among the predictors, self-efficacy was the strongest (β =  0.695). Conclusions Self-efficacy and self-esteem were key determinants of happiness in elderly people. Healthcare centers serving older populations could implement targeted interventions such as skill-building workshops aimed at enhancing self-efficacy, cognitive-behavioral therapy (CBT) sessions to build coping strategies, and art therapy programs to boost self-esteem. Additional interventions might include mindfulness and relaxation techniques to reduce stress, social engagement activities to promote a sense of belonging, and group exercises or physical activity programs that foster both physical well-being and psychological resilience. Future studies should explore the long-term effectiveness of these interventions in promoting sustained happiness in older adults.